Complications in tube thoracostomy: Systematic review and meta-analysis. Issue 2 (August 2018) - Hernandez, Matthew C.; El Khatib, Moustafah; Prokop, Larry; Zielinski, Martin D.; Aho, Johnathon M.
Abstract : BACKGROUND: Tube thoracostomy (TT) complications and their reported rates are highly variable (1–40%) and inconsistently classified. Consistent TT complication classification must be applied to compare reported literature to standardize TT placement. We aim to determine the overall TT-related complication rates in patients receiving TT for traumatic indications using uniform definitions. METHODS: Systematic review and meta-analysis was performed assessing TT-related complications. Comprehensive search of several databases (1975–2015) was conducted. We included studies that reported on bedside TT insertion (≥22 Fr) in trauma patients. Data were abstracted from eligible articles by independent reviewers with discrepancies reconciled by a third. Analyses were based on complication category subtypes: insertional, positional, removal, infection/immunologic/education, and malfunction. RESULTS: Database search resulted in 478 studies; after applying criteria 29 studies were analyzed representing 4, 981 TTs. Injury mechanisms included blunt 60% (49–71), stab 27% (17–34), and gunshot 13% (7.8–10). Overall, median complication rate was 19% (95% confidence interval, 14–24.3). Complication subtypes included insertional (15.3%), positional (53.1%), removal (16.2%), infection/immunologic (14.8%), and malfunction (0.6%). Complication rates did not change significantly over time for insertional, immunologic, or removal p = 0.8. Over time, there was a decrease in infectious TT-related complications as well as an increase in positional TT complications. CONCLUSION: Generation of evidence-based approaches to improve TT insertion outcomes is difficult because a variety of complication classifications has been used. This meta-analysis of complications after TT insertion in trauma patients suggests that complications have not changed over time remaining stable at 19% over the past three decades. LEVEL OF EVIDENCE: Systematic review and meta-analysis, level III.